Explanation in Biology - Braillard, Pierre-Alain. author. aut Link
VI, 438 p. 52 illus.
Keywords: Patterns of explanation in biology have long been recognized as different from those deployed in other scientific disciplines, especially physics. Celebrating the diversity of explanatory models found in biology, this volume details their varying types as well as their relationships to one another. It covers the key current debates in the philosophy of biology over the nature of explanation, and its apparent diversity that stems from a variety of historical, causal, mechanistic, or mathmatical explanatory practices. Offering a wealth of fresh analyses on the nature of explanation in contemporary biology chapters examine aspects ranging from the role of mathematics in explaining cell development to the complexities thrown up by evolutionary-developmental biology, where explanation is altered by multidisciplinarity itself. They cover major domains such as ecology and systems biology, as well as contemporary trends, such as the mechanistic explanations spawned by progress in molecular biology. With contributions from researchers of many different nationalities, the book provides a many-angled perspective on a revealing feature of the discipline of biology.